Not too late : the power of pushing limits at any age - Bounds, Wendy (Ballantine Books, 2024)
"An award-winning journalist tells the inspiring story of her unlikely midlife journey to master the daunting sport of obstacle course racing--a powerful, science-based account of the change possible at any age when we push limits. In her mid-forties, Gwendolyn Bounds attended a dinner party where someone asked a little girl: 'What do you want to be when you grow up?' It struck Bounds: in middle age, no one asks you that anymore. So, she put the question to herself. The answer set her on an unexpected path of transformation from an unathletic office executive glued to her screens into a competitive age group medalist and world championship competitor in obstacle racing-a demanding military-style sport requiring speed, endurance, mobility and strength. What began as a simple goal to complete a single race grew into a profound five-year quest to reconcile the realities of growing older. In Not Too Late, Bounds explores how tackling something new and hard upended her expectations for middle age--while also helping the author reconcile regrets of her youth. Her story takes us from playgrounds and gyms where Bounds relearns childhood movements (swinging from monkey bars, climbing a rope) to far-flung Spartan Race courses where she masters running in difficult terrain and conquering challenges such as scaling tall walls, crawling under barbed wire, and carrying heavy loads of rocks up mountains. Through this equally beautiful and brutal sport, Bounds discovers potent tools to combat the mental and physical risks of aging as she makes her way from newbie to the podium. Bounds' journey offers inspiration and a roadmap for anyone craving more out of life. Woven through Not Too Late are insights from scientists, longevity doctors, philosophers, elite athletes, and performance experts on how to reimagine our limits and redefine who we think we are. Through Bounds' story, as she changes her body and mindset, we learn humans' potential to tap inner reserves, face deep-rooted fears, locate intrinsic motivation, and push the boundaries of what we ask of ourselves at any life stage. Ultimately, one message prevails: When unleashing our full potential, age can be a secret weapon"--